PENGETAHUAN REMAJA DAN MOTIVASI GURU DENGAN PERILAKU SEKS BEBAS DI SMA - Ashriady Ashriady; Rosdiana Ufi (Politeknik Kesehatan Kemenkes Mamuju, 2016)
Free sex could threaten the future of adolescents, especially in the field of education. Almost all of the schools that the average level of high school (High School) in particular SMAN 4 Baubau admitted annually forced to pull out with pupils from the school because it was considered guilty. The problem of sex leading to pregnancy outside marriage and sometimes lead to abortion. The purpose of this study was aimed to determine the relationship of sex behavior in adolescents on the motivation of teachers at SMAN 4 Baubau. This research is a quantitative research with cross sectional study design. The sample in this study is 88 samples. The sampling technique used was a systematic random sampling. Data processing using the statistical test Chi Square test with a confidence level of 95% (value = 0.05). Based on the results it can be concluded that there is a relationship between knowledge students free sex (X2 = 10.728, p = 0.001), there is a correlation between students with the knowledge of free sex (X2 = 138.692, p = 0.000). It is suggested that students can improve their knowledge about sex, abiding by the religious level, by searching for a good and accurate information and can choose which friends so as not to affect the behavior of free sex. Teachers can motivate by providing knowledge about free sex, and the understanding of religion as well as provide good information and be responsible so that students are not wrong in getting information that may affect student behavior.